Quick-Wee: A Novel Non-Invasive Urine Collection Method for Infants in the Emergency Department. (1st June 2016) - Kaufman, J; Tosif, S; Fitzpatrick, P; Donath, S; Hopper, S; Bryant, P; Babl, F
Abstract: BACKGROUND: Urinary tract infection is one of the commonest paedi-atric infections, and important to diagnose or exclude in young children with fever. Limitations exist with all current urine collection methods, guidelines vary, and clinicians have different preferences. Clean catch urine (CCU) is a preferred non-invasive collection method and is convenient and painless compared to suprapubic aspirate and catheterisation. However, it can be unreliable and time-consuming, with high rates of sample contamination and collection failure. Only 12% void within 5 minutes based on recent data. An ideal method of urine collection would be fast, reliable and simple. Suprapubic stimulation may trigger involuntary parasympathetic detrusor contraction, inducing voiding via early childhood exteroceptive somato-bladder reflexes. OBJECTIVES: We conducted a pilot study using a novel method (termed 'Quick-Wee') of gentle cutaneous suprapubic stimulation with saline-soaked gauze, to hasten voiding for non-invasive urine collection. DESIGN/METHODS: Prospective pilot study of 40 pre-continent children age 1-24 months requiring CCU in a paediatric emergency department in Australia. Standard CCU was augmented by 5 minutes of suprapubic cutaneous stimulation (Quick-Wee method), with either cold (3 degrees Celsius) or room-temperature saline-soaked gauze. PRIMARY OUTCOME: Void <5 minutes. SECONDARY OUTCOMES: Successful catch of sample (if voids), contamination rate, parental/clinician satisfaction with technique. RESULTS: CONCLUSION: Gentle cutaneous suprapubic stimulation with saline-soaked gauze appears to be a promising technique with 30% voiding in <5 minutes, a rate higher than observed without such stimulation. A randomised controlled trial comparing Quick-Wee to standard CCU without suprapubic stimulation is now underway.